5.2 0.9+0.9的简便运算

5.2 *0.9+0.9=0.9*(5.2+1)=1*6.2-0.1*6.2=6.2-0.62=5.58

5.2*0.9+0.9=(5+0.2)x0.9+0.9=5x0.9+0.2x0.9+0.9=4.5+0.18+0.9=4.5+1.08=5.58 谢谢,请采纳

5.2 *0.9+0.9=0.9(5.2+1)=6.2(1-0.1)=6.2-0.62=5.58

5.2*0.9+0.9*4.8解:运用乘法分配律=(5.2+4.8)x0.9=10x0.9=9祝学习进步.

(5.20.9)+(0.9*1)=0.9*(5.2+1)=0.9*6.2=5.58

5.2 *0.9+0.9=0.9(5.2+1)=6.2(1-0.1)=6.2-0.62=5.58

5.2*0.9=5.2*(1-0.1)=5.2*1-5.2*0.1=5.2-0.52=4.68

0.9*(5.2+1)=(1-0.1)*6.2=6.2-0.62=5.58

脱式计算过程方法如下解:5.2*0.9+0.9=5.2*0.9+1*0.9=0.9*(5.2+1)=0.9*6.2=5.58

相关文档

5.2乘0.9加0.9的简便
1.25-0.125 8简便计算
4.8-4.8x0.5简便计算
56.5x9.9十56.5怎样算
5.2x0.9十0.9简便方法
3.6一3.6 0.8简便计算
3.94+34.3 0.2简便运算
5.2 0.9 5.2简便运算
yhkn.net
lpfk.net
5213.net
ymjm.net
zxqk.net
电脑版